High-performance supercapacitor materials based on polypyrrole composites embedded with core-sheath polypyrrole@MnMoO4 nanorods. (10th September 2016) - Wang, Huan; Song, Yahui; Zhou, Jingkuo; Xu, Xiaoyang; Hong, Wei; Yan, Jing; Xue, Ruinan; Zhao, Huilin; Liu, Yu; Gao, Jianping
Abstract: In this study, a binary composite polypyrrole@MnMoO4 was facilely prepared via in situ oxidative polymerization of monomer in the presence of MnMoO4 nanorods The MnMoO4 nanorods were wrapped by a layer of polypyrrole (PPy) and formed a core-sheath structure which embedded in PPy matrix. The prepared PPy@MnMoO4 composite was characterized by XRD, IR, SEM, and TEM spectroscopy and its capacitive performance was investigated. Electrochemical measurements show that the specific capacitance of PPy@MnMoO4 composite (MnMoO4 content is 13.95 wt%) reached 462.9 F g −1 at a scan rate of 5 mV s −1 and 374.8 F g −1 at a current density of 0.2 A g −1 in a three-electrode system. In the two-electrode system of a symmetric supercapacitor, it achieved specific capacitances of about 221.3 F g −1 at a scan rate of 5 mV s −1 and 207.5 F g −1 at a current density of 0.5 A g −1 . The PPy@MnMoO4 retained 80.6% of its initial capacitance after 1000 cycles. The excellent electrochemical performance of PPy@MnMoO4 composite is attributed to the synergistic effects between the polymer chain and MnMoO4 in PPy@MnMoO4 and its well-designed structure.